Localised submental abscess consequent to an infected premolar socket: a case report - Munjal, Manish; Munjal, Shubham; Budhiraja, Namrata; Talwar, Shivam; Arora, Vineeta; Kaur, Hardeep; Chawla, Deeksha; Gill, Ruchika; Gill, Zoya; Pillai, Anjana; Joshi, Tanvi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Deep neck infections either cellulitis or abscess are localised initially within the potential spaces and fascial planes of the head and neck. These infections should not be ignored. One should not underestimate the necessity of appropriate and timely treatment of deep neck infections due to the late sequel of serious and potentially life-threatening nature of these infections. An intriguing patient of a limited submental/ suprahyoid pathology secondary to suppuration in the premolar socket was addressed with timely intervention surgically.